Melintasi Ruang Perbatasan Identitas Chicano Melalui Perspektif Transnasional New Mestiza Consciousness Gloria Anzaldua - Nurul Baeti, Sovian Nisa (University of Brawijaya, 2024)
The United States of America roots its national identity to the ideals of the American Dream which admit inclusivity. This has driven a big wave of migration from Mexico which formed the Chicano community. On the other hand, the increasing wave of Mexican immigrants has caused anxiety for previous immigrants (referring to Europeans). This anxiety encourages the government to form their collective identity based on American Exceptionalism ideology which excludes people of color like Chicano. Those ideas are seen as a form of new colonialism and has led to the formation of the Chicano Literary Movement. This movement aims to merge the Chicano into the national identity of the United States and oppose the partition of typical colonial identities that emerged through the discourse of American Exceptionalism. The efforts made are to reconstruct cultural identity and restore local knowledge of the Chicano community through literary works. Therefore, this study aims to look at the reconstruction of Chicano identity attempted by Chicano writers to escape the construction of colonial identity. Rudolfo Anaya's Bless Me, Ultima and Heart of Aztlan which are the most fundamental Chicano literary works were chosen as the material objects of this study. Meanwhile, the researcher uses Gloria Anzaldua's New Mestiza Consciousness theory to see the formation of transnational identities from both novels. New Mestiza Consciousness is rooted in plural consciousness that recognizes all kinds of contradictions, ambiguities, and deviations to form a hybrid identity by destroying the duality of colonial subjects and objects. The results of this study show that Anaya attempts to present various points of view that represent the Chicano perspective, indigenous communities, and white communities. However, in the actions of his characters, Anaya still sides with indigenous identities. As a result, the Chicano identity formed is exclusive and produces a new binary partition between native and foreign. Therefore, Anaya failed to achieve mestiza consciousness and failed to break away from western (colonial) identity and knowledge.